COMPOSIÇÃO DO FITOPLÂNCTON DE REPRESA EM ÁREA AGRÍCOLA DE MATO GROSSO DO SUL - SILVA, Emily Daniela Pereira da; ABELHA, Milza Celi Fedatto; BATISTA, Douglas Camargo; KASHIWAQUI, Elaine Antoniassi Luiz (ANAIS DO ENIC, 2024)
-